Pengembangan Karir Karyawan pada Industri Garmen dan Variabel yang Mempengaruhinya - Reza Maulana Prasaja; Purnadi; Yudhistira; Arin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to find out the influence of work motivation, work training and work experience on employee career development. Challenges in career development in this company include the lack of clear, well-defined career paths. The importance of work motivation, work training and work experience to improve employee career development. This sample collection used quantitative methods. The research sample consisted of 108 employees taken based on a dense sampling technique or census. The data collection instrument used a five-level Likert scale questionnaire. Data analysis uses multiple analysis with the help of SPSS 25.00 software. Research findings show that work motivation has a positive and significant effect on employee career development, work experience has a positive and significant effect on employee career development, job training has no effect on employee career development. The company should pay attention to the motivation aspect in order to improve career development, as well as provide an understanding of the tasks given so that employees better understand and can carry out the obligations given.